Sharp Power Theory in International Relations and its Employment in Countries’ Foreign Policies - Hoshang Sabir Ahmed; Abdelfattah Rashdan (QALAAI ZANIST JOURNAL, 2021)
This study aims to address a recent phenomenon in power studies in international relations, which is the term and concept of sharp power, which appeared in late 2017 in the studies of American think tanks. The study explains sharp power by presenting the theoretical directions it dealt with, which focused on aspects of the similarities and differences between sharp power and other forms of power, which are hard power, soft power, and smart power. As well as comparing it to the terms and concepts that are used to denote modern, unconventional warfare. The study tries to discuss the tools and mechanisms of sharp power that countries with authoritarian regimes use to impose influence and hegemony on target countries, especially the soft power tools that these countries exploit to penetrate and interfere in the internal affairs of countries, and to convert the minds and hearts of their people to accept their hegemony and sovereignty, instead of attracting them, and winning their minds and hearts. The study dealt with the deficiencies of sharp power, within the ambiguity of the concept, is it the soft power of authoritarian countries, or it is the malicious use of soft power, as well as whether it is formulating terms or is it a new phenomenon of power in international relations, and the Chinese perspective on sharp power.